MATURATION AND FECUNDITY OF MUDSKIPPER BOLEOPHTHALMUS DENTATUS IN THE NORTHERN ARABIAN SEA - Hoda, S M Shamsul; Akhtar, Yasmin (Indian Journal of Fisheries, 2011)
Seven maturity stages are described in the development of gonads in themudskipper, Boleophthalmiis dentatus Cuv. Val. from Karachi. The mean lengthat first maturity, 69 mm SL in males and 72 mm SL in females, is supportedby gonosomatic index (GSI), hepatosomatic index (HSI) and condition factor(K). A sex ratio of 1.04 male : 1.00 female is observed. Length-frequencycurves indicate that the juveniles and young found in September to Decemberare the products of the same year and the juveniles measuring 45 mm SL inSeptember increases to 60 mm SL within three months. The ova-diameter polygonsIndicate that the spawning of individuals occurs twice during the periodfrom April to December, April-May and July-August. The mean fecundity is2371; variation being 970 at 75 mm SL to 4113 at 110 mm SL. Fecunditystandardlength, fecundity-total fish weight and fecundity-ovary weight relationshipsare presented